2010
DOI: 10.1177/1475921710388970
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on cable stayed bridge using health monitoring system: a case study

Abstract: The Zhanjiang Bay Bridge, located in an inner gulf of South China, is a cable stayed bridge with a main span of 480 m. An analysis on the thermal effects experienced by the bridge is presented according to a health monitoring system (HMS) that began operation in 2006. The parameters studied in the analysis include thermal time lags and gradients of the steel box girder, concrete tower, and stayed cables, as well as displacements at center span and tops of the towers. Among the findings, temperature gradient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…While the use of safety factors is widely accepted as good engineering practice, the lack of detailed knowledge about the thermal behaviour of complex bridge structures can sometimes lead to excessively over-estimated thermal movements. Even worse, despite the use of safety factors, serviceability failures such as locked expansion joints (Cao et al, 2010) or component failure (Hornby, Collins, Hill, & Cooper, 2012) can occur, leading to questions about the extreme ranges and accumulation of displacement.…”
Section: Bridge Thermal Design -Current Practice and Shortcomingsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of safety factors is widely accepted as good engineering practice, the lack of detailed knowledge about the thermal behaviour of complex bridge structures can sometimes lead to excessively over-estimated thermal movements. Even worse, despite the use of safety factors, serviceability failures such as locked expansion joints (Cao et al, 2010) or component failure (Hornby, Collins, Hill, & Cooper, 2012) can occur, leading to questions about the extreme ranges and accumulation of displacement.…”
Section: Bridge Thermal Design -Current Practice and Shortcomingsmentioning
confidence: 99%
“…However, neither of these studies considered the temperature of other structural members, which were likely to have directly influenced the deck displacement. Cao, Yim, Zhao, and Wang (2010) identified temperature distributions and time lags for various structural members of the Zhanjiang Bay Bridge (cable-stayed, 480 m main span) in China, and how these influenced the displacement of the bridge deck and towers. Since their results were based on four days of data collected during summer, the interesting findings of this study are not necessarily indicative of the general thermal behaviour of the bridge.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum effective temperature of bridge deck, main cable, and air is almost the same, while the maximum effective temperature of bridge deck is significantly higher. Cao et al [74] studied the monitored temperatures including steel deck, stayed cables, and concrete tower of the Zhanjiang Bay Bridge, located in an inner gulf of South China, and found that the maximum temperature gradient in the steel girder was more than twice the original design value. The concrete temperature lagged significantly behind ambient air by 5-6 hours, and stayed cable temperatures were between those of ambient air and concrete.…”
Section: Field Measurementmentioning
confidence: 99%
“…The abnormal change of static girder deflection indicates the occurrence of cable damage. 31,32 Hence, it is feasible that cable damage is quantified using the abnormal change of static girder deflection. For example, our previous research revealed that cable damage resulted in the abnormal change of linear correlation between static girder deflection and uniform temperature, which was used for damage quantification in the Zhijiang Bridge.…”
Section: Introductionmentioning
confidence: 99%